2005
DOI: 10.1021/om0492653
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Redox Chemistry of Ethenyl and Ethynyl Ferrocene Polyaromatic Dyads

Abstract: A series of ferrocenyl-arene dyads, Fc-CtC-Ar, trans-Fc-CHdCH-Ar, and Fc-CHd CH-CHdCH-Ar (Ar ) phenyl, 1-naphthyl, 2-naphthyl, 9-phenanthryl, 9-anthryl, 1-pyrenyl, 3-perylenyl) have been synthesized. Their structures and spectroelectrochemical properties are discussed. The molecular structures of several have been determined by X-ray diffraction and the observed structures compared with global free-energy minimized calculated structures. In the solid state all ethynyl dyads have the aromatic ring orthogonal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
71
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 54 publications
12
71
0
Order By: Relevance
“…The terminal Ph-C-H moieties of the butadiene ligand are not coplanar with the C(1)-C(4) plane but make dihedral angles of 33.7°and 35.4°with it so that both Ph groups adopt the exo configuration and are tilted towards the cyclopentadienyl ligand. In contrast, the ipso C atoms of the central Ph groups lie close to the C(1)-C(4) plane though the rings are tilted with respect to it by 64.0°for C(11) and 77.3°for C (17). The Co-C(butadiene) distances are 2.0594(15)/2.0485(15) Å to the outer C atoms and 1.9911 (15) …”
Section: [Co{g 4 -Ph(h)c(ph)c(ph)c(h)ph}{g 5 -C 5 H 4 C(o)ch 3 }] (1c)mentioning
confidence: 95%
See 1 more Smart Citation
“…The terminal Ph-C-H moieties of the butadiene ligand are not coplanar with the C(1)-C(4) plane but make dihedral angles of 33.7°and 35.4°with it so that both Ph groups adopt the exo configuration and are tilted towards the cyclopentadienyl ligand. In contrast, the ipso C atoms of the central Ph groups lie close to the C(1)-C(4) plane though the rings are tilted with respect to it by 64.0°for C(11) and 77.3°for C (17). The Co-C(butadiene) distances are 2.0594(15)/2.0485(15) Å to the outer C atoms and 1.9911 (15) …”
Section: [Co{g 4 -Ph(h)c(ph)c(ph)c(h)ph}{g 5 -C 5 H 4 C(o)ch 3 }] (1c)mentioning
confidence: 95%
“…Although the non-planarity in the case of 3d, 3e, 3h and 3i may be a consequence of crystal packing forces, it seems reasonable to assume that for 3k the distortions are due to intramolecular steric interactions between the anthracenyl group and the C(36) hydrogen atom on one hand, and the phenyl groups of the C 4 Ph 4 ligand on the other. In a related complex Fe(g 5 -C 5 H 5 )(g 5 -C 5 H 4 -CH@CH-9-anthracenyl) similar anthracene-alkene steric interactions are relieved by rotation about the C-C bond joining them so that there is an angle of 62.58 (14)°between alkene and anthracene planes [17]. The presence of the phenyl groups of the tetraphenylbutadiene ligand prevents this in 3k.…”
Section: Structures Of [Comentioning
confidence: 99%
“…Although the results reported for 1a were not encouraging [3], there was the possibility that more highly annelated PAH end-groups would prove to be better acceptors than Ph. Furthermore, our electrochemical/OTTLE studies on a series of Fc-C"C-Ar (Fc = ferrocenyl) derivatives showed they, or more particularly their [Fc-C"C-Ar] + derivatives, have unusual spectroscopic properties [5], which might also be found in their Ni(g 5 -C 5 Consequently we prepared a series of Ni(g 5 -C 5 H 5 ) (PPh 3 )-C"C-Ar complexes 1, where Ar = (a) C 6 H 5 , (b) 4-PhC 6 H 4 , (c) 1-C 10 H 7 (1-naphthyl), (d) 2-C 10 H 7 (2-naphthyl), (e) 9-C 14 H 9 (9-phenanthryl), (f) 9-C 14 H 9 (9-anthryl), (g) 3-C 16 H 9 (3-pyrenyl), (h) 1-C 20 H 11 (1-perylenyl), (i) 2-C 4 H 3 S (2-thienyl), and (j) C 10 H 9 Fe (ferrocenyl). They have been characterised by spectroscopic and electrochemical data, and the molecular structures of a number of them determined by X-ray diffraction.…”
Section: Introductionmentioning
confidence: 92%
“…4), which bounce be deferring a high-energy ligand-centred π-π * electronic transition. In initiation, a weaker absorption band in the visible region was observed at 515 nm respectively, which is to be found another localized excitation formed by two roughly degenerated transitions, and Fe(II) d-d transition or metal-ligand charge transfer (MLCT) process [15,16].…”
Section: Fig 3 Ft-ir Spectrum Of Ferrocenylorganostannoxanementioning
confidence: 87%